2018
DOI: 10.18203/issn.2455-4529.intjresdermatol20181821
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of self-medication for acne among undergraduate medical students

Abstract: <p class="abstract"><strong>Background:</strong> Acne is one of the most common inflammatory chronic skin diseases that affect teenagers and continues into adulthood. Self-medication is common among medical students. Hence this present study was undertaken to study the knowledge, attitude and practice of self-medication for acne among medical students.</p><p class="abstract"><strong>Methods:</strong> This cross-sectional study included medical students of the second ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 4 publications
3
10
0
Order By: Relevance
“…Sixty-three percent of students in our study were of the opinion that self-medication is a component of self-care, which was close to the findings of Karamata et al [6]. Around 50% of the students had no reservations about recommending the medication to their friends and family, similar to the results of Raikar et al [1]. According to our findings, 89.4% of the students thought that the dermatologist's consultation was important for the treatment of acne.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Sixty-three percent of students in our study were of the opinion that self-medication is a component of self-care, which was close to the findings of Karamata et al [6]. Around 50% of the students had no reservations about recommending the medication to their friends and family, similar to the results of Raikar et al [1]. According to our findings, 89.4% of the students thought that the dermatologist's consultation was important for the treatment of acne.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Karamata et al reported self-medication in 59.2% of acne sufferers which was close to our findings [6]. According to Raiker et al, a higher number of medical students (77.4%) practiced self-medication [1].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, 73.0% of students believe self-medication is part of self-care and 59.0% encouraged friends and family to self-medicate. Our observation is in line with the independent studies done by Tameez-Ud-Din et al and Raikar et al wherein almost 60.0% of students used self-medication for acne and recommended it to their friends [ 12 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar to present study, Raikar DR et al, found that out of 352 students, 319 suffered from acne. 12 In present study, out of 200 girls, 100 (50%) girls had mild degree of acne, 32 (16%) girls had moderate degree of acne while 10 (5%) girls had severe degree of acne (Table 4). In our study, out of 142 girls who had acne, 90 (45%) were doing self-medication while 52 (26%) of girls were not doing self-medication (Table 4).…”
Section: Discussionmentioning
confidence: 45%